"But I did not touch nobody!"—Patients' and nurses' perspectives and recommendations after aggression on psychiatric wards—A qualitative study. (10th July 2019) - Vermeulen, Jentien M.; Doedens, Paul; Boyette, Lindy‐Lou N. J.; Spek, Bea; Latour, Corine H. M.; de Haan, Lieuwe
Abstract: Aims: To gain a deeper understanding of the differences in patients and staff perspectives in response to aggression and to explore recommendations on prevention. Design: Qualitative, grounded theory study. Methods: We conducted semi‐structured interviews with patients and nurses involved in an aggressive incident. Data collection was performed from May 2016 ‐ March 2017. Results: Thirty‐one interviews were conducted concerning 15 aggressive incidents. Patients and nurses generally showed agreement on the factual course of events, there was variation in agreement on the perceived severity (PS). Patients' recommendations on prevention were mostly personally focussed, while nurses suggested general improvements. Conclusion: Patients are often capable to evaluate aggression and give recommendations on prevention shortly after the incident. Patients and nurses differ in the PS of aggression. Recommendations on prevention of patients and nurses are complementary. Impact: What problem did the study address? Perspectives of patients and nurses differ with respect to aggression, but how is unclear. What were the main findings? Patients and nurses generally described a similar factual course of events concerning the incident, patients often perceive the severity less than nurses. Patients are capable to give recommendations on prevention of aggressive incidents, shortly after the incident. Where and on whom will the research have impact? Factual course of events can be a common ground to start evaluating aggressive incidents and post‐incident review should address the severity of incidents. Asking recommendations from patients on how to improve safety and de‐escalation can lead to innovative and personal de‐escalation strategies and supports patients autonomy. Abstract : 目的: 深入理解病人与护士对待侵略性事件的观点的不同, 探索防止侵略性事件的建议。 设计: 定性的、基于理论的研究。 方法: 我们对涉及侵略性事件的病人和护士进行半结构式采访, 并在2016年5月‐2017年3月期间进行数据收集。 结果: 对涉及15起侵略性事件的31名病人和护士进行访谈。病人与护士对事件经过的事实上观点一致, 对事件严重程度的感知不一致。病人关于预防侵略性事件的建议比较偏向个人方面的预防, 护士关于预防侵略性事件的建议主要是综合性预防。 结论: 病人能够评价侵略性事件并能在事件发生后立即给出预防建议, 病人与护士对事件的严重成都的感知不一致, 但两者提出的意见互补。 影响: 此研究是为了解决什么问题?病人与护士对侵略性事件的观点不同, 不同在什么地方?此研究的主要发现是什么?与护士对事件经过的事实上观点一致, 但病人感知的事件严重程度比护士感知到的严重程度低。病人能在事件发生后立即给出预防建议。此研究将在何处对何人造成影响?事件经过可以作为评价事件的共同基础。事后回顾主要研究事件严重程度。向病人询问关于提升环境安全和防止事态扩大的建议, 会探索出创新的个性的建议同时也维护了病人的自主权。